Transmission of COVID-19 among the health personnel of the Hospital Víctor Lazarte Echegaray in Trujillo - Alfaro Angulo, Marco Antonio (2021)
Objective: To describe the characteristics of COVID-19 transmission among the health personnel. Materials and methods: A descriptive research was conducted. Data were collected through interviews, clinical-epidemiological records and medical records. The personnel who treated COVID-19 patients, and those who acquired the infection and developed symptoms were identified. The medical procedures undergone by the patients were listed. The cases were described according to the type of health personnel and epidemiological week. The absolute and relative frequencies, as well as the attack rate, were determined. The research was approved by the hospital’s research and ethics committee. Results: The diagnosis of COVID-19 was confirmed in six hospitalized patients. All of them were treated by 45 health workers in procedures such as hemodialysis, mechanical ventilation, orotracheal intubation, nebulization and upper endoscopy with no personal protective equipment. As a result, 38 individuals were infected and developed symptoms, including malaise, cough, fever and sore throat. The most affected health workers were doctors and nurses. Conclusions: In-hospital transmission of COVID-19 was evident in the health personnel, affecting most frequently doctors and nurses. The attack rate accounted for 84.44 %.